EXPLORING THE MODERN MYTHOLOGY: ANALYSING KAVITA KANE’S KARNA’S WIFE: THE OUTCAST’S QUEEN AND SITA’S SISTER - SUGUNA, S.; MALATHY, P. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
In modern-day literature, the study of mythology has presented authors with a vast and intricate framework to craft elaborate narratives that delve deeply into the intricacies of human behaviour, interpersonal connections, and societal standards. This research paper embarks on a profound and comprehensive analysis of two compelling literary works by the esteemed author Kavita Kane, explicitly focusing on Karna’s Wife: The Outcast’s Queen and Sita’s Sister. Through a meticulous and rigorous examination of the character progression depicted in Karna’s Wife, the primary objective of this study is to uncover and elucidate how Kane adeptly illustrates the transformation of Uruvi’s character, the significant relationships that shape her journey, and the innovative perspective she brings to the enigmatic persona of Karna. Simultaneously, the scrutiny of themes and symbolism in Sita’s Sister delves deeply into the core thematic foundations of the novel, the symbolic elements skilfully utilised by Kane to enhance the storyline, and the crucial influence of familial and societal expectations in moulding the characters within the narrative. By closely analysing these critical components, this research paper strives to illuminate the intricate layers of storytelling and the contemporary reinterpretation of classical mythology in Kane’s literary creations, thereby contributing to the enhanced comprehension of the enduring fascination of mythology within present-day literature.